Base Nacional Comum Curricular: sentidos, significados e saberes dos professores de Educação Física - Nardon, Tiago Aparecido (Universidade Federal de São Carlos, 2026)
This thesis investigates how teaching knowledge mediates the construction of senses and meanings attributed by Physical Education teachers to the National Common Curricular Base (BNCC). The investigation stems from the gap identified in the absence of studies analyzing the direct perspective of the teacher, assuming them as a reflective agent rather than a mere executor of curricular prescriptions. The study is characterized as qualitative, descriptive, and exploratory research organized into two stages: the descriptive phase, with the application of a questionnaire to 260 Physical Education teachers in Basic Education across all Brazilian states, and the exploratory phase, consisting of three focus groups with 15 teachers. The narratives were analyzed using Bardin's Content Analysis under the theoretical lens of Vygotsky's concepts of Sense and Meaning, Tardif's Epistemology of Practice, and Schön's Reflection-in-action and Reflection-on-action. The findings reveal that the implementation of the BNCC is a heterogeneous phenomenon mediated by a hierarchy of knowledge. Knowledge of Professional Training and Disciplinary Knowledge act as a foundation for a critical and ideological reading of the document, while Experiential Knowledge gives materiality to curricular prescriptions in the face of concrete teaching work conditions. Finally, Curricular Knowledge allows teachers to "play by the rules," preserving their institutional autonomy. The study demonstrates that teachers attribute multiple senses to the BNCC, including opposition, bureaucracy, non-adherence, legitimation, validation, systematization, and curriculum, depending on the circumstances. It concludes that the BNCC, a technical and cold document in its constitution, takes shape through the actions of teachers, whose voices reveal a pragmatic positioning towards it, indicating that any curricular policy only materializes within the subjectivity and conscious decision-making of those who operate on the school floor.

Esta tesis investiga cómo los saberes docentes median la construcción de sentidos y significados atribuidos por profesores de Educación Física a la Base Nacional Común Curricular (BNCC). La investigación parte de la brecha identificada ante la ausencia de estudios que analicen la perspectiva directa del profesor, asumiéndolo como un agente reflexivo y no como un mero ejecutor de las prescripciones curriculares. El estudio se caracteriza por ser una investigación cualitativa, de tipo descriptiva y exploratoria, organizada en dos etapas: la fase descriptiva, con la aplicación de un cuestionario a 260 profesores de Educación Física de Educación Básica de todos los estados brasileños, y la fase exploratoria, constituida por tres grupos focales con 15 docentes. Las narrativas fueron analizadas por medio del Análisis de Contenido de Bardin, bajo la lente teórica de los conceptos de Sentido y Significado de Vygotsky; Epistemología de la Práctica de Tardif; y Reflexión en la acción y sobre la acción de Schön. Los hallazgos revelan que la implementación de la BNCC es un fenómeno heterogéneo, mediado por una jerarquía de saberes. Los Saberes de la Formación Profesional y los Saberes Disciplinares actúan como base para la lectura crítica e ideológica del documento, mientras que los Saberes Experienciales otorgan materialidad a las prescripciones curriculares ante las condiciones concretas del trabajo docente. Finalmente, los Saberes Curriculares permiten a los profesores "jugar con las reglas", preservando su autonomía institucional. El estudio demuestra que los profesores atribuyen múltiples sentidos a la BNCC, entre ellos contraposición, burocracia, no adhesión, legitimación, validación, sistematización y currículo, según las circunstancias. Se concluye que la BNCC, un documento técnico y frío en su constitución, cobra forma en la acción de los docentes, cuyas voces revelan un posicionamiento pragmático en relación con ella, lo que indica que cualquier política curricular solo se concreta en la subjetividad y en la toma consciente de decisiones de quienes actúan en el día a día de la escuela.
National Common Curricular Base: meanings, significances and knowledge of Physical Education teachers
Base Curricular Común Nacional: significados, importancia y conocimientos de los profesores de Educación Física
Keywords: Educação física escolar; Saberes docentes; Sentidos e significados; Autonomia docente; School Physical Education; Teachers’ Knowledge; Senses and Meanings; Teacher Autonomy; Educación Física Escolar; Saberes Docentes; Sentidos y Significados; Autonomía Docente.; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade